Transgenic models – a scientific tool to understand exercise-induced metabolism: the regulatory role of AMPK (5′-AMP-activated protein kinase) in glucose transport and glycogen synthase activity in skeletal muscle. (1st December 2003) - Wojtaszewski, J.F.P.; Nielsen, J.N.; Jørgensen, S.B.; Frøsig, C.; Birk, J.B.; Richter, E.A.
Abstract : The AMPK (5´AMP-activated protein kinase) is becoming recognized as a critical regulator of energy metabolism. However, many of these effects in muscle metabolism have been ascribed to AMPK based on the use of the unspecific activator AICAR (5-aminoimidazole-4-carboxamide-1-β-d-ribofuranoside). Using mouse models in which AMPK activity has been specifically blocked (kinase dead) or knocked out we and others have been able to conduct studies gaining more conclusive data on the role of AMPK in muscle metabolism. In this mini-review focus is on AMPK and its regulatory role for glucose transport and GS (glycogen synthase) activity in skeletal muscle, indicating that AMPK is a GS kinase in vivo which might influence GS activity during exercise and that AMPK is involved in AICAR/hypoxia-induced glucose transport but not or only partially in contraction-stimulated glucose transport.